2018
DOI: 10.1177/0310057x1804600113
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Medical Emergency Team Calls, Cardiac Arrest Calls and Re-Admission after Intensive Care Discharge: Creation of a Tool to Identify At-Risk Patients

Abstract: We aimed to develop a predictive model for intensive care unit (ICU)-discharged patients at risk of post-ICU deterioration. We performed a retrospective, single-centre cohort observational study by linking the hospital admission, patient pathology, ICU, and medical emergency team (MET) databases. All patients discharged from the Alfred Hospital ICU to wards between July 2012 and June 2014 were included. The primary outcome was a composite endpoint of any MET call, cardiac arrest call or ICU re-admission. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Third, our model might have failed to learn from the laboratory results. However, laboratory results, which have been clinically and theoretically proven to be associated with IHCA [13,15,30], have a high feature importance in the model (Fig 4), which indicates they were successfully learned. In addition, the newer variables (i.e.…”
Section: Interpretation Of the Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Third, our model might have failed to learn from the laboratory results. However, laboratory results, which have been clinically and theoretically proven to be associated with IHCA [13,15,30], have a high feature importance in the model (Fig 4), which indicates they were successfully learned. In addition, the newer variables (i.e.…”
Section: Interpretation Of the Resultsmentioning
confidence: 97%
“…To support the necessity of preventive monitoring, prior studies found that clinical deterioration is common prior to cardiac arrest [4,5]. Based on these findings, various early warning scores have been developed, ranging from an analog model based on vital signs to a digital scoring system using both vital signs and laboratory results [6][7][8][9][10][11][12][13][14][15]. Recently, a variety of early warning scores have utilized machine learning to account for the non-linear relationships in various input variables [16][17][18].…”
Section: Relationship With Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that 21% of the discharged patients had post-ICU deterioration, including cardiac arrest, RRT calls, and readmission ( 63 ) . Patients undergoing lung transplantation and other thoracic surgery, as well as advanced age, increased severity of the disease estimated by the Acute Physiology and Chronic Health Evaluation III (APACHE III) score, bradycardia, abnormal levels of albumin in the admission to the ICU, hyperkalemia and high level of activated partial thromboplastin time (APTT) at discharge from the ICU, presented a higher risk regardless of deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of patient deterioration included bradycardia, tachypnea, pyrexia, hypotension, low mean arterial pressure, and hyperkalemia 4,5 . Recognition of early deterioration has the potential to enhance patient safety, decrease mortality rates, identify patients that need to be closely assessed by a critical care nurse or medical doctor, and potentially save lives 6 .…”
Section: Introductionmentioning
confidence: 99%